Dolores J. Christman collection of John F. Kennedy memorabilia - Christman, Dolores J., 1933-2004.
Four sets of four mint national capital sesquicentennial postage stamps signed with autopen of John F. Kennedy. Includes five positive photographs and one negative of the sets.
Collection material in English.
Keywords: Kennedy, John F. -- 1917-1963.; Postage stamps -- United States; Washington (D.C.) -- Centennial celebrations, etc